Schlacht und Struktur: von der Bedeutung der Realhistorie als Erzählelement in den simplizianischen Schriften - Löcht, Joana van de (Scientia poetica, 2018)
This article assesses how historical events play an important role for the narratological structure of Hans Jacob Christoffel von Grimmelshausen’s Simplicissimus Teutsch and Courasche. Furthermore, it asks whether it was possible for the contemporary literate reader to foresee parts of the books’ plots based on his historical knowledge. The plot devices thought to be most promising for such an analysis were descriptions of battles in which the main characters were engaged. It can be shown that battles, as datable and locatable events, allow the reader to estimate the duration between certain parts of the story line.
Gesehen am 22.01.2018